Examining the Perceived Ethical Climate and Faculty Commitment in Private Higher Secondary Schools in Nepal - Agrawal , Sarita (Journal of Productive Discourse, 2025)
This study examines the relationship between perceived ethical climate and faculty commitment in private higher secondary schools in Kathmandu and Lalitpur. It also explores the extent of the impact of different dimensions of perceived ethics on overall faculty commitment. A descriptive and analytical research design was employed, involving 464 faculty members selected through purposive sampling in Kathmandu and Lalitpur districts. Both primary and secondary data were utilized, with structured questionnaires serving as the primary data collection tool. The collected data were analyzed using SPSS and MS Excel. The findings reveal significant relationships between all three types of ethical climates (egoistic, benevolence, and principled) and faculty commitment. Benevolence has the strongest positive impact on faculty commitment, while egoistic climate shows an impact only on continuance commitment. Principled climate emerges as the most influential factor in overall faculty commitment, followed by benevolence. However, the egoistic climate exhibits a weak and insignificant relationship with the overall commitment of faculties in Nepalese private higher secondary schools. In these schools, team-oriented benevolence climates and rule-oriented principled climates foster strong emotional attachment among faculty members. The study concludes that cultivating a benevolent and principled ethical context is crucial for building a committed faculty team, emphasizing the pivotal role of ethical workplaces in fostering faculty commitment in Nepalese higher education.